2023
DOI: 10.3389/fspor.2022.1070477
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic impact of feeding prior to a 60-min bout of moderate-intensity exercise in females in a fasted state

Abstract: BackgroundThe metabolic impact of pre-exercise feeding of protein or carbohydrate on fat oxidation and energy expenditure rates, especially, in females, is poorly understood.MethodsRecreationally active females (n = 15, 32 ± 10 years, 164.8 ± 5.6 cm, 63.5 ± 9.3 kg, 23.4 ± 3.2 kg/m2) completed four testing sessions in a randomized, double-blind, crossover fashion after fasting overnight. Participants ingested isovolumetric and isoenergetic solutions containing either 25 g of whey protein, casein protein, carboh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
3
1
0
Order By: Relevance
“…Fat oxidation rates during fixed-intensity cycling were not affected by pre-exercise protein ingestion of different quantities compared to fasted exercise. The findings of this study are in line with previous studies [ 15 , 17 , 18 , 21 ]. Exercise in the fasted state, whether performed in a low muscle glycogen state or not, is accompanied with higher fat oxidation rates compared to a CHO-fed state, which is primarily due to the absence of insulin’s effect on suppressing mechanisms involved in lipolysis and beta-oxidation [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Fat oxidation rates during fixed-intensity cycling were not affected by pre-exercise protein ingestion of different quantities compared to fasted exercise. The findings of this study are in line with previous studies [ 15 , 17 , 18 , 21 ]. Exercise in the fasted state, whether performed in a low muscle glycogen state or not, is accompanied with higher fat oxidation rates compared to a CHO-fed state, which is primarily due to the absence of insulin’s effect on suppressing mechanisms involved in lipolysis and beta-oxidation [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…Resting energy expenditure was significantly elevated post-exercise, which is a common finding following moderate and high-intensity exercise [ 33 ]. We hypothesized that due to diet-induced thermogenesis following different protein doses, the protein groups would have higher post-exercise REE compared to 0 g. However, no significant differences were observed between the different doses, despite a large effect size in pre- to post-exercise change within the 40 g condition but moderate effect sizes for 0 and 20 g. Findings are somewhat similar compared to previous studies, who demonstrated significantly higher REE following pre-exercise protein compared to CHO-fed, but not compared to fasted [ 17 , 20 , 21 ]. The timing of the post-exercise measurement, might explain some discrepancies.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations